A comprehensive sintering mechanism for TBCs‐Part I: An overall evolution with two‐stage kinetics. Issue 5 (2nd March 2017) - Li, Guangrong; Xie, Hua; Yang, Guanjun; Liu, Gang; Li, Chengxin; Li, Changjiu
Abstract: A comprehensive sintering mechanism for lamellar thermal barrier coatings was reported experimentally and theoretically in this study. To begin with, an overall property evolution with two‐stage kinetics was presented during thermal exposure. The increase in mechanical property at initial thermal exposure duration (stage‐I) was much faster with respect to that in the following longer duration (stage‐II). At the stage‐I, the in situ pore healing behavior revealed that the significant faster sintering kinetics was attributed to the rapid healing induced by multipoint connection at the intersplat pore tips, as well as a small quantity of the narrow intrasplat cracks. At the following stage‐II, the residual wide intersplat pore parts and the wide intrasplat cracks decreased the possibility of multiconnection at their counter‐surfaces, resulting in a much lower sintering kinetic. Moreover, a structural model based on the microstructure of plasma sprayed YSZ coatings was developed to correlate the microstructural evolution with mechanical property. Consequently, the model predicted a two‐stage evolutionary trend of mechanical property, which is well consistent with experiments. In brief, by revealing the pore healing behavior, this comprehensive sintering mechanism shed light to the structure tailoring toward the advanced TBCs with both higher thermal‐insulating effect and longer life time.